Efficacy, Safety, and Immunogenicity of Vaccines against Viruses: From Network Medicine to Clinical Experimentation - Guzzi, Pietro Hiram; Milano, Marianna; Das, Jayanta Kumar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint emerges as a beacon guiding researchers, scientists, and medical professionals through uncharted territories. In this volume, we delve deep into the intricate world of immunization, where the fusion of bioinformatics and network medicine reshapes our understanding of vaccines' efficacy, safety, and immunogenicity.